Endurance of methanogenic archaea in anaerobic bioreactors treating oleate based wastewater - Salvador, A. F. (2009)
Methanogenic archaea are anaerobic microorganisms specialized on methane production from simple substrates such as hydrogen and acetate. These substrates are abundant in anaerobic bioreactors treating long-chain fatty acid (LCFA)-rich wastewater. LCFA are utilized by bacteria and their mineralization can be achieved by the final set of methanogenic reactions that result on methane production. However, methanogens are often reported as sensitive to LCFA concentrations what makes the anaerobic treatment of LCFA- rich wastewaters problematic. Nevertheless, successful anaerobic treatment of LCFA-rich wastewater, both in fed-batch and continuous mode, has been already reported. In the present work, the archaeal community developed during fed-batch and continuous treatment of oleate (unsaturated LCFA), in a highly efficient anaerobic reactor, was studied using molecular tools. Cloning and sequencing results showed that predominant microorganisms are closed related to Methanobacterium and Methanosaeta species. The presence of these microorganisms in the high rate anaerobic bioreactor proves that it is possible to obtain an archaeal community, with high methanogenic activity, adapted to continuous feeding of LCFA-rich wastewater.